Lifecycle Portfolio Choice With Systematic Longevity Risk and Variable Investment—Linked Deferred Annuities. Issue 3 (14th March 2013) - Maurer, Raimond; Mitchell, Olivia S.; Rogalla, Ralph; Kartashov, Vasily
ABSTRACT : This article assesses the impact of variable investment‐linked deferred annuities (VILDAs) on lifecycle consumption and portfolio allocation, allowing for systematic longevity risk. Under a self‐insurance strategy, insurers set premiums to reduce the chance that benefits paid exceed provider reserves. Under a participating approach, the provider avoids taking systematic longevity risk by adjusting benefits in response to unanticipated mortality shocks. Young households with participating annuities average one‐third higher excess consumption, while 80‐year‐olds increase consumption about 75 percent. Many households would prefer to participate in systematic longevity risk unless insurers can hedge it at a very low price.